FEASIBILITY STUDY FOR NATURE TOURISM POTENTIAL ECOTOURISM DEVELOPMENT in Buleleng - I Putu Ananda Citra (Media Komunikasi Geografi, 2015)
The research was conducted in natural tourism object Buleleng Regency with the aim 1) to describe the potential of ecotourism in natural tourism object Buleleng Regency, 2) Mapping the distribution of natural attractions that meet eligibility potential to be developed as ecotourism in Buleleng. The method used in this study is a survey supported by the observation method. Sampling by purposive sampling technique. Data was analyzed using qualitative descriptive analysis techniques. The results showed that 1) the potential of ecotourism in natural tourist attraction (Lovina and Git-Git) in Buleleng Regency have different levels of potency. Tourism object Lovina has ecotourism potential is high, while the attraction Git-Git Waterfall potential ecotourism including the middle category, 2) Distribution of natural tourism object that meet eligibility potential to be developed as ecotourism in Buleleng consists of two variations of the potential ecotourism. tourism object of Git-Git Waterfall have an appropriate level of ecotourism middle category, lack of facilities, community participation and contribution to the community is a factor that determines the appropriateness of the as ecotourism. While the attraction Lovina feasibility level to be developed as ecotourism were high, because all aspects of ecotourism already qualifies as ecotourism.Keywords: feasibility study, attractions, ecotourism